Simply brilliant powerful techniques to unlock your creativity and spark new ideas - Schroeder, Bernhard (AMACOM, 2017)
Using his CreativityWorks framework, creativity and innovation expert Bernhard Schroeder explains how to break out of your mental box, reignite natural curiosity, and move step-by-step through a set of exercises that help individuals and teams. --